9 5/6 - 2 1/3 is 7 1/2.
You could get this answer by finding the same denominator of the fractions. The LCM of both is 6. Multiply the 1 of the second fraction 2 times because you had to multiply the denominator 2 times to get to 6.
You should have 2 2/6.
Now get 9 5/6 - 2 2/6.
The answer is 7 3/6, simplifies into 7 1/2.
9 5/6 - 2 1/3 is 7 1/2.
Answer: (x+2)
Step-by-step explanation:
Answer:
x = 2, y = -1.
Step-by-step explanation:
2x - 5y = 9
3x + 4y = 2
Multiply first equation by -3 and the second by 2:
-6x + 15y = -27
6x + 8y = 4 Adding the 2 equations:
23y = -23
y = -1.
Now substitute this value for y in the first equation:
2x - 5(-1) = 9
2x = 9 +5(-1)
2x = 9 - 5
2x = 4
x = 2.